THE JUGGLE BOOK : A GRAPHIC NOVEL - Peters, Stephanie True, 1965-; Lozano, Omar (North Mankato, Minnesota : Stone Arch Books, an imprint of Capstone, 2022)
In this graphic novel loosely based on Rudyard Kipling's "The Jungle Book," an orphaned bear cub named Glee finds a new home in a traveling circus.
Keywords: Bear cubs -- Comic books, strips, etc; Bear cubs -- Juvenile fiction; Circus performers -- Comic books, strips, etc; Circus performers -- Juvenile fiction; Juggling -- Comic books, strips, etc; Juggling -- Juvenile fiction; Graphic novels; Comics (Graphic works)